Information System Development of Web Portalalumni National University: Information System Development of Web Portalalumni National University - Deden Ferdiansyah; Moh. Iwan Wahyuddin; Andrianingsih Andrianingsih (Jurnal Mantik, 2020)
National University is the oldest Private University in Jakarta and the second oldest in Indonesia which has thousands of Alumni spread across various fields. The aim is to create an alumni web portal in other words to make it easier for alumni to communicate or interact with alumni and share information. With this advantage is expected to be able to build data or information sources